Comparison of the complete genomes of two Echinochloa species: barnyard grass and jungle rice. Issue 2 (2nd January 2017) - Lee, Jeongran; Kim, Jin-Won; Lee, In-Yong; Ahn, Jong Hwa
Abstract: We sequenced and compared the complete chloroplast (cp) genomes of the two Echinochloa species; E. crus-galli (KT983256) and E. colona (KT983255). The size of complete chloroplast genomes of the two species are 139, 851 and 139, 592 base pairs in length, respectively. They include a pair of inverted repeats (22, 640 and 22, 618 bp) separated by the small (12, 518 and 12, 519 bp) and large (82, 053 and 81, 837 bp) single copy regions. Both chloroplast genomes include a total of 136 genes. Phylogenetic analysis revealed that E. colona was diverged between 2.65 and 3.18 million years ago (Mya) from the E. oryzicola and E. crus-galli .